OPTIMIZATION AND ACESSING THE INFLUENCE OF XANTHAN GUM, EFFERVESCENT COMPONENTS AND HARDNESS ON FLOATATION BEHAVIOR AND DRUG RELEASE OF GASTRO-FLOATING CAPTOPRIL TABLET - Syaiful Choiri; T.N. Saifullah Sulaiman; Ilham Kuncahyo (Indonesian Journal of Pharmacy, 2014)
This research purposed to optimize, investigate and evaluate the influence of xanthan gum, sodium bicarbonate-citric acid as effervescent components and hardness on floatation behavior and drug release of gastro-floating captopril tablet with floating system. A 23 full factorial design (8 runs) was applied to optimize the floating captopril tablet using xanthan gum (X1), ratio of effervescent components (X2) and hardness (X3) as independent variables. Optimum area was determined by superimposed contour plot of floating lag time (Y1), cumulative drug release at 60min (Q60) (Y2) and drug release constant rate (Y3) using Design Expert® software. Xanthan gum, effervescent components and hardness were affected the floatation behavior and drug release. Hardness was the most dominant factor affected the floatation behavior and drug release. Based on superimposed contour plot, the optimum area was in range of xanthan gum 58–100mg, sodium bicarbonate 45–63mg, citric acid 7–25mg and hardness at 70–98N.